Potencial fisiológico e tamanho de sementes de abóbora - Vidal, Maquiel Duarte (2007)
The objective of this study was to compare vigor tests in order to evaluate the physiological potential of seed lots, classified according to their size, of four squash species: Menina Brasileira , Caserta , Caravela , and De Tronco . First, the seed lots were submitted to germination tests, as well as to first count, accelerated aging, suboptimal temperature, cold test, evaluation of seedlings under laboratory conditions, emergence at 21 days, emergence speed index, and hypocotyls length by the emergence. Afterwards, alterations were implemented with respect to the cold test, exposing the seeds to chilling conditions for different periods (three, five, seven, and nine days). The experiments followed a totally randomized design, with four replications. The averages were compared by the Tukey test, at 5% of probability, and the influence of chilling periods by polynomial regression analysis. It was concluded that the squash seed size influences significantly the vigor, and this influence depends on the extent of the differences in terms of size among the classes. From the results, the cold test was found to be the most efficient method to stratify the vigor influence over the different classes of seed size. In addition, as for test conditions, it was concluded that the temperature have to be kept at 10°C, for seven days. What is more, the results indicate that the Pearson s correlation coefficient method was not effective for the purpose of correlating the behavior of vigor tests under laboratory conditions with the emergence of plants in a greenhouse.